2009
DOI: 10.1088/0031-9155/54/21/017
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron microbeam radiation therapy for rat brain tumor palliation—influence of the microbeam width at constant valley dose

Abstract: To analyze the effects of the microbeam width (25, 50 and 75 microm) on the survival of 9L gliosarcoma tumor-bearing rats and on toxicity in normal tissues in normal rats after microbeam radiation therapy (MRT), 9L gliosarcomas implanted in rat brains, as well as in normal rat brains, were irradiated in the MRT mode. Three configurations (MRT25, MRT50, MRT75), each using two orthogonally intersecting arrays of either 25, 50 or 75 microm wide microbeams, all spaced 211 microm on center, were tested. For each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 29 publications
2
96
1
Order By: Relevance
“…Synchrotron microbeam radiotherapy (MRT) uses wafers of microscopically narrow, synchrotron-generated X-rays for pre-clinical cancer trials in animal models [1][2][3][4][5][6]. Previous studies have shown normal tissue to be extremely tolerant to MRT at doses in considerable excess of those that were therapeutically effective [7].…”
mentioning
confidence: 99%
“…Synchrotron microbeam radiotherapy (MRT) uses wafers of microscopically narrow, synchrotron-generated X-rays for pre-clinical cancer trials in animal models [1][2][3][4][5][6]. Previous studies have shown normal tissue to be extremely tolerant to MRT at doses in considerable excess of those that were therapeutically effective [7].…”
mentioning
confidence: 99%
“…1 Experimentally discovered at the Brookhaven National Laboratory 2 and soon afterwards studied at the European Synchrotron Radiation Facilities 3,4 it was shown to have the extraordinary ability of ablating brain tumors while sparing normal tissue in a variety of animals. 5 The absorbed dose threshold for tissue damage using micrometer-width beams was on the order of 10 3 Gy, orders of magnitude higher than that for broad beam radiation. [4][5][6][7] Synchrotron microbeams are generally 25-75 μm in width and spaced 100-200 μm center to center.…”
Section: A Microbeam Radiation Therapy (Mrt)mentioning
confidence: 99%
“…5 The absorbed dose threshold for tissue damage using micrometer-width beams was on the order of 10 3 Gy, orders of magnitude higher than that for broad beam radiation. [4][5][6][7] Synchrotron microbeams are generally 25-75 μm in width and spaced 100-200 μm center to center. 6 Studies have shown normal tissue sparing effect is preserved at up to ∼700 μm beam width 8 as long as the valley doses are kept under the threshold values.…”
Section: A Microbeam Radiation Therapy (Mrt)mentioning
confidence: 99%
“…2,3 Over the years, different sizes of microbeams have been developed and used in animal studies including beam widths as small as 20 µm (Refs. [4][5][6][7] and ranging up to 700 µm, often referred to as minibeam radiation therapy. 8,9 Despite the promising animal study results, the working mechanisms of MRT are still poorly understood, hindering the potential clinical translation of this promising cancer radiation therapy.…”
Section: A Microbeam Radiation Therapymentioning
confidence: 99%